Morbidity in nocturnal asthma: sleep quality and daytime cognitive performance. Issue 8 (August 1991) - Fitzpatrick, M F; Engleman, H; Whyte, K F; Deary, I J; Shapiro, C M; Douglas, N J
Abstract : Most patients with asthma waken with nocturnal asthma from time to time. To assess morbidity in patients with nocturnal asthma nocturnal sleep quality, daytime sleepiness, and daytime cognitive performance were measured prospectively in 12 patients with nocturnal asthma (median age 43 years) and 12 age and intellect matched normal subjects. The median (range) percentage overnight fall in peak expiratory flow rate (PEF) was 22 (15 to 50) in the patients with nocturnal asthma and 4 (-4 to 7) in the normal subjects. The patients with asthma had poorer average scores for subjective sleep quality than the normal subjects (median paired difference 1.1 (95% confidence limits 0.1, 2.3)). Objective overnight sleep quality was also worse in the asthmatic patients, who spent more time awake at night (median difference 51 (95% CL 8.1, 74) minutes), had a longer sleep onset latency (12 (10, 30) minutes), and tended to have less stage 4 (deep) sleep (-33 (-58, 4) minutes). Daytime cognitive performance was worse in the patients with nocturnal asthma, who took a longer time to complete the trail making tests (median difference 62 (22, 75) seconds) and achieved a lower score on the paced serial addition tests (-10 (-24, -3)). Mean daytime sleep latency did not differ significantly between the two groups (2 (-3, 7) minutes). It is concluded that hospital outpatients with stable nocturnal asthma have impaired sleep quality and daytime cognitive performance even when having their usual maintenance asthma treatment.